1996
DOI: 10.1007/bf00129733
|View full text |Cite
|
Sign up to set email alerts
|

Feeding of nutrients delays apoptotic death in fed-batch cultures of recombinant NSO myeloma cells

Abstract: The addition of concentrated nutrient solutions in fed-batch cultures of recombinant GS-NS0 cells delays the onset of apoptosis by 24 to 48 hours and decreases the specific rate of apoptotic death approximately two-fold. This decrease in apoptosis appears primarily responsible for the increase in culture longevity that results in five-to ten-fold increases in final product concentrations in fed-batch cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
24
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 11 publications
2
24
1
Order By: Relevance
“…However, since CHO cells are mainly cultivated in serumfree, fed-batch cultures in a large-scale bioreactor in industries, effects of nutrient addition to CHO cell cultures on autophagy induction need to be further investigated. Previously, there have been numerous reports on nutrient feeding strategies that have shown to delay apoptotic death during cell culture (Bibila and Robinson, 1995;DiStefano et al, 1996;Reuveny et al, 1986;Zhou et al, 1997). Also, there have been reports that amino acid re-addition inhibited autophagic vacuoles formation (Kovacs et al, 1981), and adding low concentrations of amino acids to hepatocytes stimulated the phosphorylation of p70S6K, which is known to inhibit autophagy (Blommaart et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, since CHO cells are mainly cultivated in serumfree, fed-batch cultures in a large-scale bioreactor in industries, effects of nutrient addition to CHO cell cultures on autophagy induction need to be further investigated. Previously, there have been numerous reports on nutrient feeding strategies that have shown to delay apoptotic death during cell culture (Bibila and Robinson, 1995;DiStefano et al, 1996;Reuveny et al, 1986;Zhou et al, 1997). Also, there have been reports that amino acid re-addition inhibited autophagic vacuoles formation (Kovacs et al, 1981), and adding low concentrations of amino acids to hepatocytes stimulated the phosphorylation of p70S6K, which is known to inhibit autophagy (Blommaart et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…There have also been other attempts to reduce starvation-induced PCD in mammalian cell culture by adding amino acid mixtures, growth factors, or chemical reagents (DiStefano et al, 1996;Franek, 1995;Mastrangelo and Betenbaugh, 1998). Previously, Meneses-Acosta et al (2001) compared the phenotypes of cell death in Sf9 insect cells with hybridoma cells, mentioning autophagy, observed by multiple stages of phagosomes upon glucose limitation, as a part of PCD during insect cell culture.…”
Section: Introductionmentioning
confidence: 97%
“…While such strategies may indeed improve productivity, they also involve retention of the protein of interest within the culture environment for extended periods of time. Furthermore, in such pulsed-batch or fed-batch cultures, it has also been reported that cells still die from apoptotic death (DiStefano et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro culturing of hybridoma cells has been extensively studied for a high production rate of monoclonal antibody for several decades, and many efficient nutrient feeding strategies have been developed (Glacken 1987;Bibila and Robinson 1995;Distefano et al 1996;Birch and Racher 2006). The most important strategy for doing fed-batch culture is to reduce the formation of byproducts, such as lactate and ammonia, and keep the nutrient concentration balanced and stable.…”
Section: Introductionmentioning
confidence: 99%
“…Their production can be partly decreased by reducing the glucose and glutamine concentrations in the medium. In recent studies, effective cultures of hybridoma and Chinese hamster ovary (CHO) cells have been developed through comprehensive research on nutrient metabolism (Bibila and Robinson 1995;Distefano et al 1996;Birch and Racher 2006). The models in these studies incorporated not only major pathways of glucose and glutamine metabolism but also pathways of other amino acids into the stoichiometric model.…”
Section: Introductionmentioning
confidence: 99%